Mycotoxins in poultry feed and feed ingredients in Nigeria - Akinmusire, Oyekemi O. (Mycotoxin Res, 2018)
Mycotoxins are toxic secondary fungal metabolites that can negatively affect animal productivity when ingested through feed. In order to assess mycotoxin contamination of poultry feed and feed ingredients vis-a-vis source tracking of feed contamination in Nigeria, 102 samples of feed (n = 30) and feed ingredients (n = 72) were collected from in-house mills of poultry farms across 12 states of Nigeria and analyzed for multiple mycotoxins using LC/MS-MS. One hundred and forty microbial metabolites were detected in the feed and feed ingredients. The most frequent mycotoxin in the feed was fumonisin B(1), occurring in 97% of the samples at mean concentration of 1014 μg kg(−1). AFB(1) occurred in 83% of the feed samples at mean concentration of 74 μg kg(−1) and in all feed ingredients except fish meal and other cereals (millet and rice). Feed samples analyzed in this study were contaminated with at least four mycotoxins: aflatoxins and fumonisin co-occurring in 80% of the samples. Peanut cake and maize contributed the most to the levels of aflatoxin and fumonisin, respectively, in the feed. Consequently, there is a need to explore other cereal- and protein-based ingredients for compounding feeds in order to reduce the risk associated with high mycotoxin (e.g. aflatoxin) intake in poultry. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12550-018-0337-y) contains supplementary material, which is available to authorized users.